Origins and traditions in comparative education: challenging some assumptions. Issue 1 (2nd January 2018) - Manzon, Maria
ABSTRACT: This article questions some of our assumptions about the history of comparative education. It explores new scholarship on key actors and ways of knowing in the field. Building on the theory of the social constructedness of the field of comparative education, the paper elucidates how power shapes our scholarly histories and identities.